An immune evasion mechanism with IgG4 playing an essential role in cancer and implication for immunotherapy. Issue 2 (20th August 2020) - Wang, Hui; Xu, Qian; Zhao, Chanyuan; Zhu, Ziqi; Zhu, Xiaoqing; Zhou, Junjie; Zhang, Shuming; Yang, Tiqun; Zhang, Biying; Li, Jun; Yan, Meiling; Liu, Renming; et al.
Abstract : Background: Recent impressive advances in cancer immunotherapy have been largely derived from cellular immunity. The role of humoral immunity in carcinogenesis has been less understood. Based on our previous observations we hypothesize that an immunoglobulin subtype IgG4 plays an essential role in cancer immune evasion. Methods: The distribution, abundance, actions, properties and possible mechanisms of IgG4 were investigated with human cancer samples and animal tumor models with an extensive array of techniques both in vitro and in vivo. Results: In a cohort of patients with esophageal cancer we found that IgG4-containing B lymphocytes and IgG4 concentration were significantly increased in cancer tissue and IgG4 concentrations increased in serum of patients with cancer. Both were positively related to increased cancer malignancy and poor prognoses, that is, more IgG4 appeared to associate with more aggressive cancer growth. We further found that IgG4, regardless of its antigen specificity, inhibited the classic immune reactions of antibody-dependent cell-mediated cytotoxicity, antibody-dependent cellular phagocytosis and complement-dependent cytotoxicity against cancer cells in vitro, and these effects were obtained through its Fc fragment reacting to the Fc fragments of cancer-specific IgG1 that has been bound to cancer antigens. We also found that IgG4 competed with IgG1 in reacting to Fc receptors of immune effector cells. Therefore, locally increased IgG4 in cancer microenvironment should inhibit antibody-mediated anticancer responses and help cancer to evade local immune attack and indirectly promote cancer growth. This hypothesis was verified in three different immune potent mouse models. We found that local application of IgG4 significantly accelerated growth of inoculated breast and colorectal cancers and carcinogen-induced skin papilloma. We also tested the antibody drug for cancer immunotherapy nivolumab, which was IgG4 in nature with a stabilizing S228P mutation, and found that it significantly promoted cancer growth in mice. This may provide an explanation to the newly appeared hyperprogressive disease sometimes associated with cancer immunotherapy. Conclusion: There appears to be a previously unrecognized immune evasion mechanism with IgG4 playing an essential role in cancer microenvironment with implications in cancer diagnosis and immunotherapy.